In praise of Ophelia: an interpretation of Pessoa's only love - Severino, Alexandrino E. (Alexandrino Eusébio); Jennings, H. D. (Hubert Dudley) (Pessoa Plural, 2013)
Based on a presentation by Alexandrino E. Severino at the First International Symposium on Fernando Pessoa in 1977, this essay (written by Severino in conjunction with Hubert Jennings) was prepared for publication in the volume of symposium proceedings, eventually entitled The Man Who Never Was. Because permission to quote from Ophelia's letters to Fernando (all of them unpublished at the time) was ultimately denied, this essay was not published then or, for that matter, later. The evidence, drawn from Ophelia's side of the correspondence, attests to Ophelia's honest and honorable behavior during the two phases of her love affair with the poet.